Saúde e espiritualidade na Faculdade de Medicina de Botucatu: trajetória de 2003 a 2015 - Silva, Carlos Eduardo Capelasso da [UNESP]; Daher, Solange Ramires [UNESP]; Moraes, Lucas Barbosa Napolitano de [UNESP]; Prado, Priscilla Dias [UNESP]; Gomes, Patricia [UNESP]; Masci, Irene Pinto Silva [UNESP]; Santos, Lara Cristina Antunes dos [UNESP]; Moreno, Marcus Vinicius [UNESP]; Silva, Nuno Emanuel de Oliveira Figueiredo da [UNESP]; Andrade, Luís Gustavo Modelli [UNESP]; Cavalcante, Ricardo Souza [UNESP]; Banin, Vanessa Burgugi [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
Introduction: spirituality is recognized as a factor that contributes to the health of many people. The spirituality of the health implications have been studied scientifically and documented in hundreds of articles and growing number of medical schools, national and international, either with optional discipline or even the mandatory disciplines. The School of Medicine of Botucatu / UNESP has since 2003 activities that emphasize interactions between health and spirituality. In 2009 these activities were organized in the form of a university extension project entitled: "Health and Spirituality". Objective: To encourage studies, scientific research and assistance activities in the area of health and spirituality in an integration scenario from academia to society in order to promote better health and well-being to human being as an integral being: body, mind and spirit. Methods: The following activities are performed: Ecumenical Spiritual Support Group with the patients hospitalized in the HC-UNESP, group studies issues related to the interaction health and spirituality, scientific research, courses and conferences in this area. Results: The project enables reflection, studies, research and support of its members in the health and spirituality area, as well as a broader view on health, and application of spirituality in clinical practice. Since its formalization as a university extension project in 2009, it owned a total of 03 fellows (graduate students in Medicine), and from the beginning of its activities (2003), more than 80 active members have been through the project (among undergraduate students medicine and other courses, faculty and staff of FMB / UNESP and community members), plus more than 1,300 people have participated in at least some of the activities promoted by the project, especially courses and conferences. It takes place also encourage research and publications in this area.

Introdução: a espiritualidade é reconhecida como um fator que contribui para a saúde de muitas pessoas. As implicações da espiritualidade na saúde vêm sendo estudadas cientificamente e documentadas em centenas de artigos e em número cada vez maior de escolas médicas, nacionais e internacionais, seja com disciplina optativa ou mesmo obrigatória dos currículos médicos. A Faculdade de Medicina de Botucatu/ UNESP possui desde 2003 atividades que contemplam a interação saúde e espiritualidade. Em 2009 essas atividades organizaram-se sob a forma de um projeto de extensão universitária intitulado: “Saúde e Espiritualidade”. Objetivo: estimular estudos, pesquisas científicas e atividades de assistência na área de saúde e espiritualidade, em um cenário de integração do meio acadêmico com a sociedade, no intuito de promover mais saúde e bem-estar ao ser humano, como ser integral: corpo, mente e espírito. Materiais e métodos: são realizadas as seguintes atividades: Grupo Ecumênico de Apoio Espiritual junto aos pacientes internados nas enfermarias do HC-UNESP, Grupo de estudos de temas relacionados à interação saúde e espiritualidade, pesquisas científicas, cursos e congressos nessa área. Resultados: O projeto possibilita reflexão, estudos, pesquisas e assistência dos seus integrantes na área de saúde e espiritualidade, além de uma visão mais abrangente sobre a saúde, e aplicação da espiritualidade na prática clínica. Desde sua formalização como projeto de extensão universitária em 2009, possuiu um total de 03 bolsistas (alunos da graduação em Medicina), e desde o início de suas atividades (2003), mais de 80 membros ativos já passaram pelo projeto (entre alunos de graduação de medicina e outros cursos, docentes e funcionários da FMB/UNESP e membros da comunidade), além de mais de 1300 pessoas já participaram de pelo menos alguma das atividades promovidas pelo projeto, principalmente cursos e congressos. Realiza-se também incentivo a pesquisa e publicações nessa área.
Keywords: Saúde; Espiritualidade; Medicina; Saúde; Espiritualidade; Medicina